Viking heritage and history in Europe
1 online resource (xiv, 248 pages).
Keywords: Viking Heritage and History in Europe presents new research and perspectives on the use of the Vikings in public history, especially in relation to museums, re-creation, and re-enactment in a European context. Taking a critical heritage approach, the volume provides new insights into the re-creation of history, imagining the past, interpretation, ambivalence of authenticity, authority of History, remembrance and memory, medievalism, and public history. Highlighting the complexity of the field of public history today, the fourteen chapters all engage with questions of historical authenticity and authority. The volume also critically examines the public⁰́₉s reception, engagement with, and interpretation of the Viking Age and the concepts of who these individuals were. Each chapter illuminates an aspect of these themes in relation to museums, leisure activities, politics, tourism, re-enactment, and popular culture ⁰́₃ all from the vantage point of Viking cultural heritage. Viking Heritage and History in Europe is one of the first volumes to examine the use and role of the Vikings within the field of public history, both past and present. The book will be of interest to those engaged in the study of heritage, public history, history, the Vikings, vikingism, medievalism, and media history.